2012
DOI: 10.1021/nl2045759
|View full text |Cite
|
Sign up to set email alerts
|

Full Surface Embedding of Gold Clusters on Silicon Nanowires for Efficient Capture and Photothermal Therapy of Circulating Tumor Cells

Abstract: We report on rapid thermal chemical vapor deposition growth of silicon nanowires (Si NWs) that contain a high density of gold nanoclusters (Au NCs) with a uniform coverage over the entire length of the nanowire sidewalls. The Au NC-coated Si NWs with an antibody-coated surface obtain the unique capability to capture breast cancer cells at twice the highest efficiency currently achievable (~88% at 40 min cell incubation time) from a nanostructured substrate. We also found that irradiation of breast cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 31 publications
(54 reference statements)
1
85
1
Order By: Relevance
“…Hemocytometer was used to count cells and according dilution was subsequently pursued to reach a cell concentration around 10 5 /mL. 19 The cell concentration was selected also for ensuring the yield of a large result data pool to reach a reliable conclusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemocytometer was used to count cells and according dilution was subsequently pursued to reach a cell concentration around 10 5 /mL. 19 The cell concentration was selected also for ensuring the yield of a large result data pool to reach a reliable conclusion.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, nanostructures with size ranging from 30 to 1150 nm have been employed for CTCs isolation, and high efficiency was reported in all cases. For instance, 88% of cancer cells were captured onto antibody immobilized silicon nanowires (SiNWs) with diameter of 50–160 nm; 19 high isolation efficiency up to 95% was reported on antibody grafted silicon nanopillars (NPs) with diameter in the range of 100–200 nm; 20 cancer cell isolation efficiency on antibody grafted spherical particles with diameter of 232 nm was 4–5 times higher than on a flat surface. 21 Nanostructured surfaces with halloysite nanotubes was also demonstrated to enhance the CTC recruitment with a three-fold increase for MCF7 cells, while nonspecific leukocytes adhesion was prevented.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, compared with free AuNPs, Shen demonstrated that pSi/HAuNSs generated much more heat to efficiently destroy breast cancer cells in vitro and xenografted tumor in vivo. In 2012, Su et al and Park et al further described the use of the AuNPs and gold nanoclusters (AuNCs)-decorated SiNWs as photothermal agents to destroy cancer cells under NIR light irradiation (808 nm) [25,26]. KB cancer cells treated with PEG-AuNPs@ SiNWs (150 μg/ml) were all destroyed through 3-min exposure of 808 nm NIR laser at the power density of 2 W/cm 2 , and all of the MCF-7 cells captured by the AuNCs-SiNWs were killed after an NIR light irradia- Reproduced with permission from [19,24].…”
Section: Silicon Nanomaterial-based Nanoagents For Cancer Therapymentioning
confidence: 99%
“…First, we describe typical kinds of silicon nanomaterialbased biosensors (e.g., field-effect transistors [FET] and surface-enhanced Raman scattering [SERS] sensors), enabling ultrahighly sensitive detection of cancer markers (e.g., proteins, tumor-suppressor genes and telomerase activity, among others) [20][21][22][23]. Second, we introduce the latest progress in the development of silicon nanomaterial-based nanoagents for cancer chemotherapy and phototherapy applications in vitro and in vivo [13,19,[24][25][26][27][28][29][30][31]. Finally, we discuss the challenges and opportunities in this promising field.…”
mentioning
confidence: 99%
“…5.10). Meanwhile, Park et al reported gold nanoclusters (AuNCs)-coated SiNWs as a substrate for concurrent capture and phototherapy of tumor cells [68]. In their work, to capture tumor cells with high specificity, specific antibody was first conjugated with the AuNC-coated SiNWs.…”
Section: Photothermal Therapymentioning
confidence: 99%